On the classification of complex multi-germs of corank one and codimension one - Houston, Kevin (MATHEMATICA SCANDINAVICA, 2005)
Corank one multi-germs $f:(C^n,S)→ (C^p,0)$, $n<p$, of $\mathcal A_e$-codimension one are classified. The mono-germs are given in an explicit normal form and the multi-germs are described in terms of augmentations, and concatenations of mono-germs and a special bi-germ.